Chronic Nasal Administration of Kisspeptin-54 Regulates Mood-Related Disorders Via Amygdaloid GABA in Hemi-Parkinsonian Rats - Osman Sinen; Ayşegül Gemici Sinen; Narin Derin; Mutay Aydın Aslan (Balkan Medical Journal)
Background: Depression and anxiety, the most prevalent neuropsychiatric manifestations in Parkinson’s disease (PD), negatively impact their quality of life. Aims: To determine whether the chronic nasal administration of kisspeptin-54 (KP-54) could. Alleviate symptoms of anxiety and depression in hemi-Parkinsonian rats. Study Design: Experimental study. Methods: This study included adult Sprague Dawley male rats who were administered either a vehicle (artificial cerebrospinal fluid) or 6-hydroxydopamine (6-OHDA) unilaterally into the medial forebrain bundle. The vehicle, or KP-54 (3 nmol/kg, applied topically to the rhinarium), was administered daily for a seven-day period. The sucrose preference test (SPT), elevated plus maze test (EPMT), and open field test (OFT) were implemented to evaluate depression- and anxiety-like behaviors, respectively, seven days following the lesion surgery. Gamma-aminobutyric acid (GABA) concentrations in the amygdala were quantified using mass spectrometry. Tyrosine hydroxylase in substantia nigra was analyzed using immunohistochemistry. Results: The nasal delivery of KP-54 significantly reduced depression- and anxiety-like behaviors that were induced by 6-OHDA, as indicated by the results of the SPT, OFT, and EPMT. Moreover, it was observed that nasal KP-54 effectively mitigated 6-OHDA-induced motor deficits and the loss of nigral dopaminergic neurons. The nasal administration of KP-54 augmented the decline in GABA levels in the amygdala induced by 6-OHDA. Furthermore, effective correlations were established between GABA concentrations and behavioral parameters. Conclusion: The nasal delivery of KP-54 could function as a viable therapeutic alternative for treating mood-related disorders in PD.